An adsorptive photo-Fenton-like removal of 1, 2-benzisothiazolin-3-one by NH2-MIL-53(Fe) under simulated solar light. (14th April 2023) - Sun, Peifu; Zhang, Xiao; Guo, Zhiren; Liu, Xinyue; Lan, Yuanming; Zhang, Dongxiang; Li, Hansheng; Li, Jinying; Liu, Helei; Xu, Xiyan
Abstract : Schematic diagram of the BIT adsorptive photo-Fenton-like degradation mechanism over NH2 -MIL-53(Fe) under solar light irradiation. Abstract : The excessive discharge of isothiazolinone bacteriostatic agent-containing wastewater has posed serious threats to human health and environmental safety. As 1, 2-benzisothiazolin-3-one (BIT) is one of the most commonly used isothiazolinones, its effective degradation is necessary and urgent. In the current study, a NH2 -MIL-53(Fe)-based adsorptive photo-Fenton-like system was constructed for efficiently adsorbing and photodegrading BIT under solar light. The equilibrium BIT adsorption capacity Q e of NH2 -MIL-53(Fe) reached 1140.89 mg g −1 . The adsorptive photo-Fenton-like system has achieved more than 90% removal of BIT using NH2 -MIL-53(Fe) in the presence of H2 O2 under solar light irradiation, and the band gap of NH2 -MIL-53(Fe) was calculated by UV-Vis analysis to be 2.10 eV. The influences of pH, dosage of photocatalysts and H2 O2 were also assessed. It was found that H2 O2 reduced the recombination of electron–hole pairs, and the radical quenching experiments and EPR testing result confirmed that h +, ˙OH and O2 ˙ − played a crucial role in the photocatalytic process. This study supports the application of Fe-based MOF materials for simultaneous adsorption and the solar light photocatalytic degradation of BIT.